The Sarrazin effect: the presence of absurd statements in conspiracy theories makes canonical information less plausible - Raab, Marius H.; Auer, Nikolas; Ortlieb, Stefan A.; Carbon, Claus-Christian (Frontiers in Psychology, 2013)
Reptile prime ministers and flying Nazi saucers—extreme and sometimes off-wall conclusion are common ingredients of conspiracy theories. While individual differences are a common research topic concerning conspiracy theories, the role of extreme statements in the process of acquiring and passing on conspiratorial stories has not been regarded in an experimental design so far. We identified six morphological components of conspiracy theories empirically. On the basis of these content categories a set of narrative elements for a 9/11 story was compiled. These elements varied systematically in terms of conspiratorial allegation, i.e., they contained official statements concerning the events of 9/11, statements alleging to a conspiracy limited in time and space as well as extreme statements indicating an all-encompassing cover-up. Using the method of narrative construction, 30 people were given a set of cards with these statements and asked to construct the course of events of 9/11 they deem most plausible. When extreme statements were present in the set, the resulting stories were more conspiratorial; the number of official statements included in the narrative dropped significantly, whereas the self-assessment of the story’s plausibility did not differ between conditions. This indicates that blatant statements in a pool of information foster the synthesis of conspiracy theories on an individual level. By relating these findings to one of Germany’s most successful (and controversial) non-fiction books, we refer to the real-world dangers of this effect.